Impact of Pre-sowing Seed Treatments on Seed Germination, Plant Establishment and Yield of Sorghum - V.S. GIRASE; V.D. SHENDE; A.D. DUMBRE; R.S. SHAIKH (Seed Research, 2026)
Present investigation was undertaken in order to know the impact of pre-sowing seed treatments on germination, seedling establishment and yield in sorghum genotype 2077 B. The different pre-sowing seed treatments showed differential response for all the nine characters. Pooled analysis of three years data indicated that the T, treatment i.e. hydration of seed for 17 h and drying at room temperature below 25°C followed by dry dressing with 0.25% thiram was superior for laboratory germination (86% & 77%), field establishment (145 plant & 139 plants), days to maturity (109 days & 112 days) and yield/ha (3789 kg & 3169 kg) in fresh as well as revalidated seed lot, respectively. Similar response was observed for this treatment during individual years also.